Novos adsorventes para aplicação na remoção de enxofre de combustíveis - Oliveira, Katherine Carrilho de (2015)
Currently the market requires increasingly pure oil derivatives and, with that, comes the need for new methods for obtaining those products that are more efficient and economically viable. Considering the removal of sulfur from diesel, most refineries uses catalytic hydrogenation process, the hydrodesulfurization. These processes needs high energy content and high cost of production and has low efficiency in removing sulfur at low concentrations (below 500 ppm). The adsorption presents itself as an efficient and economically viable alternative in relation to the techniques currently used. With that, the main purpose of this work is to develop and optimize the obtaining of new adsorbents based on diatomite, modified with two non ionic surfactants microemulsions, adding efficiency to the material, to its application on removal of sulfur present in commercial diesel. Analyses were undertaken of scanning electron microscopy (SEM), x-ray diffraction (XRD), x-ray fluorescence (XRF), thermogravimetry (TG) and N2 adsorption (BET) for characterization of new materials obtained. The variables used for diatomite modification were: microemulsion points for each surfactant (RNX 95 and UNTL 90), microemulsion aqueous phase through the use or non-use of salts (CaCl2 and BaCl2), the contact time during the modification and the contact form. The study of adsorption capacity of materials obtained was performed using a statistical modeling to evaluate the influence of salt concentration in the aqueous phase (20 ppm to 1500 ppm), finite bath temperature (25 to 60° C) and the concentration of sulphur in diesel. It was observed that the temperature and the concentration of sulphur (300 to 1100 ppm) were the most significant parameters, in which increasing their values increase the ability of modified clay to adsorb the sulphur in diesel fuel. Adsorption capacity increased from 0.43 to mg/g 1.34 mg/g with microemulsion point optimization and with the addition of salts.